(untitled) (Dermatology Reports, 2022)
Periungual warts are commonly resistant to treatment, especially in immunocompromised patients. Many treatment modalities have been used with variable results. Bleomycin is one of the most effective treatments for recalcitrant warts, including the periungual type. It can be used either as a topical application after needling or as a direct injection. We report complete clearance of multiple periungual warts in an immunocompromised patient after diluted bleomycin injection. The patient did not have a recurrence after eight months of follow up.